Improvement of operational characteristics of aircrafts by using angle position meter relative to the stream - Гринчишин, Ю. Л.; Дронь, Н. М. (Proceedings of National Aviation University (archive), 2000)
Considered are the problems of unstable laminal flow around airodynamic surfaces. It is proposed to stabilize aircrafts by means of adaptation of their control system to the position ralative to flow. Described is the primary information pick-up with wide band and increased measurements accuracy. Given are recommendations as to the choice of pick-up sensitive element and its installation on the aircraft